2017
DOI: 10.21873/invivo.11193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Bacteriuria and Pyuria on Intravesical Recurrence in Patients with Upper Tract Urothelial Carcinoma Undergoing Radical Nephroureterectomy

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Many demographic factors and clinical features were analyzed as risk factors for bacteriuria in cancer patients in this study, however, no evidence was found to support the association between bacteriuria and demographic and clinical features of the cancer patients (P > 0.05). Correspondingly, in other studies [ 24 26 ] reported that neither of the factors and clinical features mentioned in our study had no effect on the occurrence of bacteriuria.…”
Section: Discussionsupporting
confidence: 74%
“…Many demographic factors and clinical features were analyzed as risk factors for bacteriuria in cancer patients in this study, however, no evidence was found to support the association between bacteriuria and demographic and clinical features of the cancer patients (P > 0.05). Correspondingly, in other studies [ 24 26 ] reported that neither of the factors and clinical features mentioned in our study had no effect on the occurrence of bacteriuria.…”
Section: Discussionsupporting
confidence: 74%
“…Jeon et al [ 12 ] assessed 176 patients with UTUC and found that preoperative pyuria was associated with a higher risk for IVR. By contrast, Fukushima et al [ 13 ] analyzed 97 patients and asserted that pyuria could lower the risk for IVR after RNUx. Moreover, Milojevic et al [ 14 ] assessed 319 patients and suggested that preoperative pyuria was not correlated with IVR in patients with UTUC.…”
Section: Discussionmentioning
confidence: 99%
“…First, this was a retrospective study with possible selection bias, and further well-designed studies are required to confirm these results. Second, the definition of pyuria varies among studies, and even if we exclude bacteriuria, there are conditions other than tumors, such as inflammation or autoimmune diseases, that can cause pyuria [ 6 7 9 10 11 12 13 14 ]. Third, the reason neoadjuvant chemotherapy increased the risk for tumor recurrence is most likely because the patients with a history of neoadjuvant chemotherapy had a biased advanced cancer profile ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations